2007
DOI: 10.1002/jgm.1091
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of scratching behavior by silencing an endogenous cyclooxygenase‐1 gene in the skin through the administration of siRNA

Abstract: We have demonstrated the successful silencing of endogenous gene expression in the skin using the intradermal transfection of unmodified siRNA via electroporation. Using this method, we revealed that COX- 1-mediated prostaglandins may act as endogenous inhibitors of scratching behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…38,39 Such data have led to a proposed clinical trial using siRNA directed against keratin genes in patients with dominant-negative keratin disorders. 40 Other groups have reported effects of siRNAs delivered to skin by electroporation 41,42 or by cream-emulsified preparations of siRNA 43 as well as in human organotypic skin models, 44 supporting potential future use of synthetic siRNAs in skin. However, recent striking reports exploring gene-regulatory efficacy of synthetic siRNAs directed against vascular endothelial growth factor in the eye have demonstrated that therapeutic effects of sequencespecific RNA agents administered as ex vivo synthesized RNAs are not necessarily triggered by sequence-specific degradation of mRNA.…”
Section: Discussionmentioning
confidence: 98%
“…38,39 Such data have led to a proposed clinical trial using siRNA directed against keratin genes in patients with dominant-negative keratin disorders. 40 Other groups have reported effects of siRNAs delivered to skin by electroporation 41,42 or by cream-emulsified preparations of siRNA 43 as well as in human organotypic skin models, 44 supporting potential future use of synthetic siRNAs in skin. However, recent striking reports exploring gene-regulatory efficacy of synthetic siRNAs directed against vascular endothelial growth factor in the eye have demonstrated that therapeutic effects of sequencespecific RNA agents administered as ex vivo synthesized RNAs are not necessarily triggered by sequence-specific degradation of mRNA.…”
Section: Discussionmentioning
confidence: 98%
“…Further supporting its anti-pruritic actions, both pharmacological inhibition and in vivo silencing of cyclooxygenase COX1 resulted in (among else) decreased PGD2 levels and enhanced the scratching behavior in NC/Nga mice, a murine model of AD [123,124].…”
Section: Inflammatory Mediators As Peripheral Itch Sensitizersmentioning
confidence: 80%
“…Topical introduction of siRNA into the skin by intradermal injection (Wang et al, 2007a,b) or electroporation (Inoue et al, 2007) had been performed at a dosage of 20 g or 12.5 g, respectively. Moreover, topical application of antisense oligonucleotides against IL-10 has been done at 120 g (Sakamoto et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is difficult to deliver siRNA into the skin by conventional methods based on passive diffusion (simple swabbing or application of a patch) because siRNA is a hydrophilic macromolecule. Recently, it was reported that intradermal injection or electroporation could be used to deliver siRNA directly into the skin (Wang et al, 2007a,b;Inoue et al, 2007). However, these methods are invasive or require special devices.…”
Section: Introductionmentioning
confidence: 98%